Analisis Penggunaan QRIS di Jconnect Mobile Guna Memudahkan Transaksi Nasabah: Studi Kasus Bank Jatim Syariah Cabang Kota Kediri - Muhammad Faris Al Hafidh (Institut Agama Islam YPBWI Surabaya, 2023)
The increasingly tight competition in the banking business has encouraged bank institutions to provide excellent service to exceed customer expectations. E-Channel products are electronic media-based service products. This study aims to determine the marketing strategy of EChannel products at Bank Jatim Syariah Kediri Branch Office. Field Research approach whose primary data is data derived from the field. Based on the results of this study, it is known that the produc E-Channel owned by Bank Jatim Syariah Kediri Branch Office are: ATM, Mobile Banking, SMS Banking, Internet Banking, Kartu Flazz Bank Jatim Syariah, Kartu PNS Elektronik, E-Samsat Jatim, Bank Jatim Syariah Virtual Account.